Extracurricular enterprise and entrepreneurship activity : a global and holistic perspective - Preedy, Sarah; Beaumont, Emily (Contemporary issues in entrepreneurship research., 2024)
The time is pertinent for a review of enterprise and entrepreneurship extracurricular activity. An experience outside the classroom that enables students to benefit from learning through experimentation and experience, take leadership of their learning journeys, and participate in activities tailored to their entrepreneurial ambitions. Reviewing the growth and development of enterprise and entrepreneurship extracurricular activities within Higher Education Institutions (HEIs) globally, Extracurricular Enterprise and Entrepreneurship Activity considers the form these activities take - their benefits and impacts upon participants, institutions, and the wider community. The authors shine a light on an underrepresented area of enterprise and entrepreneurship education to encourage discussion and development of practice and policy, but also to fuel appreciation and understanding of the topic. Contemporary Issues in Entrepreneurship Research is an official book series of the Institute for Small Business and Entrepreneurship (ISBE). Each volume is designed around a specific theme of importance to the entrepreneurship and small business community with articles collectively exploring and developing theory and practice in the field.